1991
DOI: 10.1111/j.1469-7610.1991.tb00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Perception and the Control of Spatially Coordinated Action of Deaf and Hearing Children

Abstract: From birth onwards, auditory stimulation directs and intensifies visual orientation behaviour. In deaf children, by definition, auditory perception cannot take place and cannot, therefore, make a contribution to visual orientation to objects approaching from outside the initial field of view. In experiment 1, a difference in catching ability is demonstrated between deaf and hearing children (10-13 years of age) when the ball approached from the periphery or from outside the field of view. No differences in cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 22 publications
2
35
0
2
Order By: Relevance
“…Several studies have reported that deaf children display atypical performance on visual-motor integration tasks as well as other perceptual-motor tasks involving balance, running, throwing, and figure drawing (Erden, Otman & Tunay, 2004;Savelsbergh, Netelenbos & Whiting, 1991;Wiegersma & Van der Velde, 1983). In fact, more than 50 years ago, Myklebust and Brutten (1953) carried out one of the earliest studies investigating the visual perception skills of deaf children.…”
Section: Divergence Of Fine Vs Gross Motor Skillsmentioning
confidence: 99%
“…Several studies have reported that deaf children display atypical performance on visual-motor integration tasks as well as other perceptual-motor tasks involving balance, running, throwing, and figure drawing (Erden, Otman & Tunay, 2004;Savelsbergh, Netelenbos & Whiting, 1991;Wiegersma & Van der Velde, 1983). In fact, more than 50 years ago, Myklebust and Brutten (1953) carried out one of the earliest studies investigating the visual perception skills of deaf children.…”
Section: Divergence Of Fine Vs Gross Motor Skillsmentioning
confidence: 99%
“…Auditory information can facilitate the pick-up of visual information [3]. Auditory stimulus maintains the activation of visual stimuli in the memory [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors reported that audition is important in orienting eye, head, and body in the environment. Infants are capable of directing their eyes and head to auditory targets [1,3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognized that perceptual motor development is closely tied to the emergence of spoken language in normal hearing children and children with hearing loss [5][6][7][8][9]. Some studies have suggested that early deafness is associated with atypical development of visuomotor skills such as figure copying/drawing and catching [10,11]. We examined whether visuomotor skills of deaf children were predictive of speech and language outcomes with a CI.…”
Section: Introductionmentioning
confidence: 98%